2005
DOI: 10.1039/b512021g
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent, bifunctional dendrimers prepared by click chemistry

Abstract: Unsymmetrical dendrimers, containing both mannose binding units and coumarin fluorescent units, have been prepared using click chemistry and shown to be highly efficient, dual-purpose recognition/detection agents for the inhibition of hemagglutination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
305
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 444 publications
(317 citation statements)
references
References 29 publications
1
305
0
11
Order By: Relevance
“…As a result, the synthetic methodology to obtain these structures can be seen as complicated, giving rise to tedious purification procedures. The group of Hawker et al 37 reported in 2005 a robust and simplified synthetic protocol for the construction of unsymmetrical dendrimers by taking advantage of the efficiency and orthogonality of the CuAAC reaction. In this strategy, two types of dendrons were grown using anhydride chemistry; one dendron comprised acetylene in the core and the other an azide.…”
Section: Unsymmetrical Dendrimersmentioning
confidence: 99%
“…As a result, the synthetic methodology to obtain these structures can be seen as complicated, giving rise to tedious purification procedures. The group of Hawker et al 37 reported in 2005 a robust and simplified synthetic protocol for the construction of unsymmetrical dendrimers by taking advantage of the efficiency and orthogonality of the CuAAC reaction. In this strategy, two types of dendrons were grown using anhydride chemistry; one dendron comprised acetylene in the core and the other an azide.…”
Section: Unsymmetrical Dendrimersmentioning
confidence: 99%
“…Click chemistry has been widely used as a novel green chemistry in recent years [32][33][34][35][36][37][38][39][40]. click chemistry provides an extensively approach to quickly synthesized new polymer brushes in highly yields without special purification and serious reaction condition.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] The target compounds were synthesized by using click chemistry. [33,34] The three azide dendrons were reacted with the bis-MPA dendron in the presence of Na-ascorbate and Cu(II)SO4 in H2O/THF/DMSO solvent mixture.…”
Section: Introductionmentioning
confidence: 99%